PENGAWASAN BADAN LINGKUNGAN HIDUP TERHADAP LIMBAH INDUSTRI SAGU DI KABUPATEN KEPULAUAN MERANTI (Studi Kasus Desa Sungai Tohor Kecamatan Tebing Tinggi Timur) - Mukarromi, Al; ", Ishak (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Industrial waste pollution sago which is still going on until now caused Responsible Business does not do waste management corresponding environmental quality standards, industries sago which have yet to Installation Wastewater Management (WWTP) so that the waste material waste dumped directly into rivers and seas, a phenomenon the other is still a lot of sago industry do not yet have permission Environmental Management and Environmental Monitoring effort (UKL-UPL). Based on the phenomenon that occurs, the formulation of this research is how the Environment Agency Monitoring Implementation of the industrial waste sago and any factors that hinder the implementation of the surveillance. This study aims to find out How fatherly supervision of the Environmental Agency of the sago industry waste and its management. This study uses qualitative descriptive type of research analysis. Tekinik data collection is interview, observation and documentation. Key informants of this research is the Environmental Agency Kepuluan Meranti district in the supervision of industrial waste sago and responsible for the business. Based on the results of the study show that not maximal supervision and has not touched all existing sago industry. This is evident from the breach responsible for the business of the management of waste that is not suitable environmental quality standards, the issue of environmental permit, waste pollution phenomenon unresolved, Settings responsible for the business in the reporting of Environmental Management Document every persemseternya. And a lack of traction sanction given to the industries sago wrongdoing. as well as effective supervision have not influenced the inhibiting factors such as factors supporting means of supervision, the number of competent personnel and experts, access and long distances, as well as the commitment of the person in charge of the effort. Keywords: Monitoring, Waste Sago, Environmental Quality Standards